2019
DOI: 10.1007/s00705-019-04161-9
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis of small-ruminant lentiviruses in Polish flocks reveals the existence of a novel subtype in sheep

Abstract: Small-ruminant lentivirus (SRLV) infections are widespread in Poland, and circulation of subtypes A1, A12, A13, A16, A17, B1 and B2 has been documented. The aim of this study was to characterize the SRLV strains circulating in sheep and goats in mixed flocks in the Malopolska region, where the highest seroprevalence has been detected. Phylogenetic analysis revealed that most of the isolates from sheep belonged to subtype A13, suggesting that this subtype may be predominant in the Malopolska region. Furthermore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 25 publications
4
19
0
Order By: Relevance
“…A similar observation was already made by Olech et al who classified the genotype C strains within genotype B after sequence analysis of smaller fragments in the gag region. Kuhar et al, on the other hand, found the genotype C strains to form separate groups in both phylogenetic trees based on longer gag-pol and pol sequences but not as long as seen in this study [18,19]. A similar observation is made for some of our Belgian strains.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…A similar observation was already made by Olech et al who classified the genotype C strains within genotype B after sequence analysis of smaller fragments in the gag region. Kuhar et al, on the other hand, found the genotype C strains to form separate groups in both phylogenetic trees based on longer gag-pol and pol sequences but not as long as seen in this study [18,19]. A similar observation is made for some of our Belgian strains.…”
Section: Discussionsupporting
confidence: 85%
“…During analysis of the presented phylogenetic trees, it can be observed that the classification of strains to a specific subgroup can differ depending on the fragment that is analyzed. In the gag-pol phylogenetic tree, the strain belonging to subtype A19 is clearly separated from other genotype A subtypes [19], while in the pol tree, it clusters within subtype A1. A similar observation can be made when looking at the reference strains known to belong to genotype C. In the phylogeny based on the pol fragment, these indeed form a separate cluster, but when looking at the gag-pol sequence, they would be classified as genotype B strains.…”
Section: Discussionmentioning
confidence: 98%
“…For example, subtype A16 was found only in Germany and Poland 12 . Subtype A21, the most common subtype in the North of Germany, is genetically close to subtype A18 13 in Poland. A study by Olech et al 13 mentioned an epidemiological linkage between the small ruminants of Germany and Poland after the Second World War, which is supported by our results.…”
Section: Discussionmentioning
confidence: 99%
“…Genotype A is the most heterogeneous group and has so far been subdivided into 20 subtypes, A1 to A20 4,8-15 . Two recently published studies have to be noted, one by Olech et al 13 that defines SRLV subtype A18, and the other by Colitti et al 15 that defines SRLV subtypes A18 and A19. In the present study, the SRLVs found by Colitti et al 15 are renamed from ' A18' to ' A19' and from ' A19' to ' A20' .…”
mentioning
confidence: 99%
“…These viruses belong to the Retroviridae family, Lentivirus genera, and they share a similar viral structure (Minguijon et al, 2015) and high genetic variability (Brinkhof, 2008;Herrmann-Hoesing, 2010). Small ruminant lentiviruses (SRLVs) were classified into 5 genotypes and several subtypes (Shah et al, 2004;Deubelbeiss et al, 2014;Daneş et al, 2016;Olech et al, 2019). MV and CAE are not of public health concern but they are quite important because they can decrease productions.…”
Section: Introductionmentioning
confidence: 99%